2012
DOI: 10.1063/1.4754454
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and electronic properties of Fe and Ni codoped SnO2

Abstract: We have investigated Fe and Ni codoping effect into SnO2. Room-temperature diluted ferromagnetic semiconductors with the enhancement of magnetization can be prepared in case of codoping. The saturation magnetization can be controlled by means of the Fe and Ni codoping ratios. The electronic structures were investigated by x-ray absorption spectroscopy (XAS) and Mössbauer spectrometry. Fe3+ states were revealed by the isomer shift values. XAS revealed Ni2+ states, which suggests that the double-exchange-like fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 24 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…According to the EDS results, the nonstoichiometric formula for the (In 1−x Fe x ) 2 O 3 films with x = 0.03, 0.07, and 0.09 were determined to be (In 0 . 9 38 So, as shown in Table 2, the higher T 0 with Fe doping should lead to suppress the hopping probability of carrier and improve the stabilization of BMPs, which augmenting ferromagnetism rather weaken it. Actually, we considered that, according to the ρ−T and MR results, although the reduction in localization radius ξ with Fe doping, the enhancing T 0 and s−d exchange interaction will have more positive influence on ferromagnetism, and should be the reason that increasing the M S in our (In 1−x Fe x ) 2 O 3 films.…”
Section: Resultsmentioning
confidence: 96%
“…According to the EDS results, the nonstoichiometric formula for the (In 1−x Fe x ) 2 O 3 films with x = 0.03, 0.07, and 0.09 were determined to be (In 0 . 9 38 So, as shown in Table 2, the higher T 0 with Fe doping should lead to suppress the hopping probability of carrier and improve the stabilization of BMPs, which augmenting ferromagnetism rather weaken it. Actually, we considered that, according to the ρ−T and MR results, although the reduction in localization radius ξ with Fe doping, the enhancing T 0 and s−d exchange interaction will have more positive influence on ferromagnetism, and should be the reason that increasing the M S in our (In 1−x Fe x ) 2 O 3 films.…”
Section: Resultsmentioning
confidence: 96%
“…It is therefore deduced that the Fe-Ni codoping enhances the Ms not by the segregation of secondary phases but by the exchange interaction. [20] In the case of Fe-V codoped SnO2, Fe-V codoping also enhanced the Ms, which showed the maximum Ms at 1 % V and 1 % Fe codoping. With further increase of Fe-V codoped into SnO2 host, the Ms decreased.…”
Section: Sno2 Codoped With Two Transition Metal Ionsmentioning
confidence: 96%
“…A codoping technique that employs different d electron numbers becomes essential for the stabilization of ferromagnetism with the control of both saturation magnetization (Ms) and the coercive field (Hc) at RT. [20] Fe ION IMPLANTED SnO2 FILM [ [24] SnO2 film implanted with 5 × 10 16 Fe ions / cm 2 at 500 °C shows Kerr effect as shown in Figure 11. It is transparent Fe doped SnO2 film with high electric resistance.…”
Section: Sno2 Codoped With Two Transition Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the theoretical prediction by Dietl et al of RT ferromagnetism in ZnO-based DMSs [4], various TM elements (Fe, Co, Ni, Mn, Cr) doped wide-band-gap oxide semiconductors appear to be rather promising candidates. Experimental works on TM-doped-ZnO [5][6][7], TiO 2 [8][9][10], SnO 2 [11,12] as well as In 2 O 3 [13][14][15] in bulk, thin film and nano-particle forms have suggested that TMs certainly could be used to dope in host oxide semiconductors to achieve RT ferromagnetism for practical application. Being one of these candidate hosts, In 2 O 3 is an important n-type directband-gap semiconductor ($3.75 eV) with excellent electrical conductivity and high optical transparency.…”
Section: Introductionmentioning
confidence: 99%